Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Let's solve this problem step-by-step:
1. Determine the slope of the line:
We have two points [tex]$(-4, -2)$[/tex] and [tex]$(2, 0)$[/tex]. The formula for the slope, [tex]\( m \)[/tex], between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is given by:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Plugging in the coordinates, we get:
[tex]\[ m = \frac{0 - (-2)}{2 - (-4)} = \frac{0 + 2}{2 + 4} = \frac{2}{6} = \frac{1}{3} \][/tex]
So, the slope of the line is [tex]\( \frac{1}{3} \)[/tex].
2. Find the y-intercept of the line:
We can use the point-slope form of the line equation, [tex]\( y = mx + b \)[/tex], to determine the y-intercept [tex]\( b \)[/tex]. Substituting [tex]\( m = \frac{1}{3} \)[/tex] and one of the given points, say [tex]\((-4, -2)\)[/tex]:
[tex]\[ -2 = \frac{1}{3}(-4) + b \][/tex]
Solving for [tex]\( b \)[/tex]:
[tex]\[ -2 = -\frac{4}{3} + b \][/tex]
Add [tex]\(\frac{4}{3}\)[/tex] to both sides:
[tex]\[ -2 + \frac{4}{3} = b \][/tex]
Convert [tex]\(-2\)[/tex] to a fraction with a common denominator of 3:
[tex]\[ -\frac{6}{3} + \frac{4}{3} = b \][/tex]
This gives:
[tex]\[ b = -\frac{6}{3} + \frac{4}{3} = -\frac{2}{3} \][/tex]
Thus, the y-intercept [tex]\( b \)[/tex] is [tex]\( -\frac{2}{3} \)[/tex].
3. Determine the value of [tex]\( a \)[/tex] such that the point [tex]\( (a, 1) \)[/tex] lies on the line:
We know the point [tex]\( (a, 1) \)[/tex] lies on the line, so we can use the line equation [tex]\( y = \frac{1}{3}x - \frac{2}{3} \)[/tex] and set [tex]\( y \)[/tex] to 1:
[tex]\[ 1 = \frac{1}{3}a - \frac{2}{3} \][/tex]
Add [tex]\(\frac{2}{3}\)[/tex] to both sides to isolate the term involving [tex]\( a \)[/tex]:
[tex]\[ 1 + \frac{2}{3} = \frac{1}{3}a \][/tex]
Convert 1 to a fraction with a common denominator of 3:
[tex]\[ \frac{3}{3} + \frac{2}{3} = \frac{1}{3}a \][/tex]
Simplify:
[tex]\[ \frac{5}{3} = \frac{1}{3}a \][/tex]
Multiply both sides by 3 to solve for [tex]\( a \)[/tex]:
[tex]\[ a = 5 \][/tex]
Therefore, the value of [tex]\( a \)[/tex] is [tex]\(\boxed{5}\)[/tex].
1. Determine the slope of the line:
We have two points [tex]$(-4, -2)$[/tex] and [tex]$(2, 0)$[/tex]. The formula for the slope, [tex]\( m \)[/tex], between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is given by:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Plugging in the coordinates, we get:
[tex]\[ m = \frac{0 - (-2)}{2 - (-4)} = \frac{0 + 2}{2 + 4} = \frac{2}{6} = \frac{1}{3} \][/tex]
So, the slope of the line is [tex]\( \frac{1}{3} \)[/tex].
2. Find the y-intercept of the line:
We can use the point-slope form of the line equation, [tex]\( y = mx + b \)[/tex], to determine the y-intercept [tex]\( b \)[/tex]. Substituting [tex]\( m = \frac{1}{3} \)[/tex] and one of the given points, say [tex]\((-4, -2)\)[/tex]:
[tex]\[ -2 = \frac{1}{3}(-4) + b \][/tex]
Solving for [tex]\( b \)[/tex]:
[tex]\[ -2 = -\frac{4}{3} + b \][/tex]
Add [tex]\(\frac{4}{3}\)[/tex] to both sides:
[tex]\[ -2 + \frac{4}{3} = b \][/tex]
Convert [tex]\(-2\)[/tex] to a fraction with a common denominator of 3:
[tex]\[ -\frac{6}{3} + \frac{4}{3} = b \][/tex]
This gives:
[tex]\[ b = -\frac{6}{3} + \frac{4}{3} = -\frac{2}{3} \][/tex]
Thus, the y-intercept [tex]\( b \)[/tex] is [tex]\( -\frac{2}{3} \)[/tex].
3. Determine the value of [tex]\( a \)[/tex] such that the point [tex]\( (a, 1) \)[/tex] lies on the line:
We know the point [tex]\( (a, 1) \)[/tex] lies on the line, so we can use the line equation [tex]\( y = \frac{1}{3}x - \frac{2}{3} \)[/tex] and set [tex]\( y \)[/tex] to 1:
[tex]\[ 1 = \frac{1}{3}a - \frac{2}{3} \][/tex]
Add [tex]\(\frac{2}{3}\)[/tex] to both sides to isolate the term involving [tex]\( a \)[/tex]:
[tex]\[ 1 + \frac{2}{3} = \frac{1}{3}a \][/tex]
Convert 1 to a fraction with a common denominator of 3:
[tex]\[ \frac{3}{3} + \frac{2}{3} = \frac{1}{3}a \][/tex]
Simplify:
[tex]\[ \frac{5}{3} = \frac{1}{3}a \][/tex]
Multiply both sides by 3 to solve for [tex]\( a \)[/tex]:
[tex]\[ a = 5 \][/tex]
Therefore, the value of [tex]\( a \)[/tex] is [tex]\(\boxed{5}\)[/tex].
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.